1993
DOI: 10.1073/pnas.90.6.2399
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors of human immunodeficiency virus integrase.

Abstract: In an effort to further extend the number of targets for development of antiretroviral agents, we have used an in vitro integrase assay to investigate a variety of MATERIALS AND METHODS Materials. HIV-1 integrase protein (3.5 pmol per reaction), produced via an Escherichia coli expression vector as described (13), was obtained from R. Craigie (Laboratory of Molecular Biology, National Institute of Diabetes and Digestive and Kidney Diseases) and stored at -70°C in 1 M NaCl/20 mM Hepes, pH 7.6/1 mM EDTA/1 mM d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
211
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 272 publications
(214 citation statements)
references
References 34 publications
1
211
1
1
Order By: Relevance
“…In recent years, CAPE has attracted increasing scientific interest due to its various pharmacological activities, e.g., anticancer/tumor [2][3][4][5][6], antiviral [7,8], anti-inflammatory [9][10][11][12][13], antioxidant [14][15][16][17], cytoprotection, [18][19][20][21][22] and vasorelaxant effects [23,24]. The pharmacological effects and mechanisms of CAPE have been comprehensively reviewed recently [25].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, CAPE has attracted increasing scientific interest due to its various pharmacological activities, e.g., anticancer/tumor [2][3][4][5][6], antiviral [7,8], anti-inflammatory [9][10][11][12][13], antioxidant [14][15][16][17], cytoprotection, [18][19][20][21][22] and vasorelaxant effects [23,24]. The pharmacological effects and mechanisms of CAPE have been comprehensively reviewed recently [25].…”
Section: Introductionmentioning
confidence: 99%
“…It also exhibits significant anti-viral activity with little cytotoxicity in primary human peripheral blood mononuclear cells (PBMC) culture 6,7 . Therefore, CAPE is a potential lead for further structural optimization as potent IN inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid phenethyl ester (CAPE) especially has been found in propolis and has a broad spectrum of biological activities, including antimicrobial, antiinflammatory, antioxidant, and antitumor activities (Bankova, 2005); it also has an inhibitory effect on HIV-1 integrase, cyclooxygenase, and lipooxygenase (Fesen et al, 1993;Michaluart et al, 1999;Nicklaus et al, 1997;Sud'ina et al, 1993). It has been reported that the ester part of CAPE is important for its antiproliferative effect on various human tumor cells (Nagaoka et al, 2003).…”
Section: Introductionmentioning
confidence: 99%